The Problematic Legal Status of Baitul Maal wa Tamwil between Cooperatives and Limited Liability Companies from Legal and Sharia Perspectives - FA, Jalaluddin; Latif, Mukhtar; Muhammad, Pauzi; Wildan FA, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the problematic legal entity status of Baitul Maal wa Tamwil (BMT) between cooperatives and limited liability companies from the perspectives of positive law and Sharia principles. Following the enactment of Law Number 1 of 2013 concerning Microfinance Institutions, BMT is normatively required to be incorporated as either a cooperative or a limited liability company. This provision raises juridical and conceptual issues because BMTs possess unique characteristics as Sharia microfinance institutions with a dual function: a social function (baitul maal) and a business function (baitul tamwil) oriented toward the economic empowerment of small and medium-sized communities. This research employs a normative juridical method with a statutory and conceptual approach. The analysis is conducted on the laws and regulations governing BMTs, cooperatives, and limited liability companies, as well as relevant legal doctrines and Sharia economic principles. The results indicate that the cooperative legal form is juridically and sociologically more aligned with the character and objectives of BMTs, as it is based on the principles of kinship, member participation, and collective welfare (maslahah). Conversely, the profit-oriented nature of limited liability companies, which prioritizes shareholder interests, potentially creates a conflict of objectives and weakens the social mission and Sharia compliance of BMTs. The novelty of this research lies in its critical analysis of the implications of legal entity choice, viewed not merely as a legal-formal issue but as a determining factor for institutional identity and Sharia compliance within the national legal system. This study recommends the need for more specific regulatory restructuring to ensure the sustainability of BMTs as Sharia financial institutions based on community empowerment.